Uncoupling hepatic insulin resistance – hepatic inflammation to improve insulin sensitivity and to prevent impaired metabolism-associated fatty liver disease in type 2 diabetes - Niranjan, Sitara; Phillips, Brett E.; Giannoukakis, Nick (Frontiers in Endocrinology, 2023)
Diabetes mellitus is a metabolic disease clinically-characterized as acute and chronic hyperglycemia. It is emerging as one of the common conditions associated with incident liver disease in the US. The mechanism by which diabetes drives liver disease has become an intense topic of discussion and a highly sought-after therapeutic target. Insulin resistance (IR) appears early in the progression of type 2 diabetes (T2D), particularly in obese individuals. One of the co-morbid conditions of obesity-associated diabetes that is on the rise globally is referred to as non-alcoholic fatty liver disease (NAFLD). IR is one of a number of known and suspected mechanism that underlie the progression of NAFLD which concurrently exhibits hepatic inflammation, particularly enriched in cells of the innate arm of the immune system. In this review we focus on the known mechanisms that are suspected to play a role in the cause-effect relationship between hepatic IR and hepatic inflammation and its role in the progression of T2D-associated NAFLD. Uncoupling hepatic IR/hepatic inflammation may break an intra-hepatic vicious cycle, facilitating the attenuation or prevention of NAFLD with a concurrent restoration of physiologic glycemic control. As part of this review we therefore also assess the potential of a number of existing and emerging therapeutic interventions that can target both conditions simultaneously as treatment options to break this cycle.